Studi Teknis Eksplorasi Pemboran Aspal Buton pada PT. Gema Consultant Indonesia, Kabupaten Buton - Arjun Alus; Gaswin; Somel; Asrim (Jurnal Riset Teknik Pertambangan, 2025)
Abstract. Buton asphalt drilling exploration is an essential stage in obtaining technical data to evaluate the potential and characteristics of buton asphalt resources. This study analyzes the technical implementation of Buton asphalt drilling exploration conducted by PT Gema Consultant Indonesia in Buton Regency, focusing on operational stages and drilling performance. The research employs a descriptive quantitative approach supported by qualitative analysis. Qualitative analysis is used to describe drilling stages and operational mechanisms, while quantitative analysis is applied to calculate drilling performance parameters. The results show that the drilling activities consist of determining drilling locations, equipment mobilization and preparation, drilling operations, cycle time calculation, core recovery, measurement of drilling speed and effectiveness, core extraction and arrangement in core boxes, sample description, and installation of markers. Quantitatively, drilling performance indicates an average cycle time of 5.24 hours within an 8-hour working period, a drilling speed of 3.89 m/hour, drilling effectiveness of 65.5%, and drilling productivity of 2.55 m/hour. Drilling was conducted using the rotary drilling method with a Yanmar TF155R engine and Semi Jacrow drilling equipment. Drilling performance is influenced by equipment conditions, operator skills, and local geological characteristics. This study provides a technical reference for natural asphalt drilling exploration in areas with similar geological conditions. Abstrak. Eksplorasi pemboran aspal Buton merupakan tahapan yang sangat penting dalam memperoleh data teknis yang diperlukan untuk mengevaluasi potensi dan karakteristik sumber daya aspal Buton. Penelitian ini mengkaji pelaksanaan teknis eksplorasi pemboran aspal Buton yang dilakukan oleh PT Gema Consultant Indonesia di Kabupaten Buton melalui analisis tahapan operasional dan kinerja pemboran. Pendekatan yang digunakan adalah deskriptif kuantitatif dengan dukungan analisis kualitatif. Analisis kualitatif digunakan untuk mendeskripsikan tahapan dan mekanisme pemboran, sedangkan analisis kuantitatif digunakan untuk menghitung parameter kinerja pemboran. Hasil penelitian menunjukkan bahwa tahapan teknis pemboran meliputi penentuan titik bor, moving dan persiapan alat, proses pemboran, penghitungan waktu siklus (cycle time), core recovery, pengukuran kecepatan dan efektivitas pemboran, pengeluaran dan penataan core pada core box, deskripsi sampel dan pemasangan patok. Secara kuantitatif, kinerja pemboran menghasilkan cycle time sebesar 5,24 jam dari 8 jam kerja, kecepatan pemboran 3,89 m/jam, efektivitas pemboran 65,5%, dan produktivitas pemboran 2,55 m/jam. Kegiatan pemboran dilakukan menggunakan metode rotary drilling dengan peralatan utama berupa mesin Yanmar TF155R dan alat bor Semi Jacrow. Kinerja pemboran dipengaruhi oleh kondisi peralatan, keterampilan operator, serta karakteristik geologi setempat. Studi ini memberikan gambaran teknis yang dapat menjadi acuan dalam kegiatan eksplorasi pemboran aspal alam pada kondisi geologi yang serupa.